Impedimetric Analysis of Trabecular Bone Based on Cole and Linear Discriminant Analysis - Wei, Wenzuo; Shi, Fukun; Kolb, Juergen F. (Frontiers in Physics, 2021)
A spatially unambiguous characterization of electrical properties of osseous tissues is important for the therapy of osteopathy via electrical stimulation. Accordingly, the study aimed to discriminate the highly inhomogeneous composition and structures of different anatomical regions of trabecular bone based on their electrical properties. The electrical properties of 64 porcine trabecular bone samples were analyzed in a parallel plate electrode configuration and compared with published results. Therefore, a novel method, combining traditional Cole-Cole models with a Linear Discriminant Analysis (LDA), was developed to discriminate the different regions, i.e. femur head, greater trochanter and femur neck. Possible mechanism behind the distinction for different regions could be interpreted from both methods. Respective adjacent regions with similar structure and composition could be distinguished from statistical significant differences of Cole parameters, i.e. α (p < 0.01) and R∞ (p < 0.05). The latter was correlated especially with water content, indicating an association of individual differences in microstructures in particular with conductivity. Conversely, different regions were unambiguously discriminated with LDA based on permittivity or conductivity. Contributions to the discrimination were explicitly reflected by the coefficients of the derived LDA features. A clear distinction was obtained especially for a frequency response at 950 kHz. Moreover, predictions for the classification of unspecified samples assigned them correctly to their origin with a success of 92.9%. The combination of both methods offers the possibility for a spatial resolved and eventually patient specific discrimination and evaluation of bone tissues and their response to therapies, notable electrical stimulation.